Agroindústria: espacio educativo en los institutos federales de educación - Ana Sara Castaman; Flávia da Rosa Silveira (Universidade Federal de Rondônia, 2020)
This essay aims to discuss about the importance of agribusiness as an educational space in Vocational and Technological Education (EPT), since in several Federal Institutes of Education this sector has been used to teach theoretical/practical classes to high school students. Integrated. To this end, the methodological procedures were selected in order to conduct a research anchored in the bibliographic technique and case study and is divided into three parts: (1) concept, classification and fundamentals of agro-industries; (2) agro-industry as a teaching space and formation of the student, its relationship with work as an educational principle in the Federal Institutes of Education, Science and Technology (IF); and (3) the actions taken in the agroindustry at IFCatarinense - Santa Rosa do Sul campus. It was noticed that the agroindustry through Practical classes in Integrated High School courses have served as an excellent educational space, assisting the IF in its commitment to education and preparing students to meet the growing demand in the agro-industrial sector.